Discrimination, Social Identity, and Durable Inequalities - Hoff, Karla; Pandey, Priyanka (American Economic Review, 2006)
What are the mechanisms by which societal discrimination affects individual achievement, and why do the effects of past discrimination endure once legal barriers are removed? We report the findings of two experiments in village India that suggest that the mechanisms of discrimination operate, in part, within the individuals who are members of the groups who have been discriminated against. We demonstrate that publicly revealing an individual’s membership in such a group alters his behavior in ways that make the effects of past discrimination persist over time. A growing literature in social psychology on stereotype threat finds that stereotyped-based expectations affect individual performance in the domain of the stereotype. A study by Jeff Stone et al. (1999) is illustrative. When college students were asked to perform a task described as diagnostic of “natural athletic ability,” blacks—stereotyped as better athletes, but worse students than whites—performed better than whites. When the same test was presented as diagnostic of “sports intelligence,” the performance of blacks declined, that of whites improved, and the racial gap was reversed. Evidence suggests that a mediating factor in stereotype threat is a change in self confidence (Mara Cadinu et al., 2005) In our studies, we investigated whether the public revelation of social identity (caste) affects cognitive task performance and responses to economic opportunities by young boys in village India. Subjects were sixth and seventh graders drawn from the two ends of the caste hierarchy. We asked subjects to learn and then perform a task under incentives, and we manipulated whether their peers in the experimental session knew their caste. Caste is well-suited to this manipulation because, unlike race, gender, and ethnicity, there are no unambiguous outward markers of caste among young boys. Six subjects, generally from six different villages, participated in each experimental session. In the control condition, the subjects were anonymous within the six-person group. In the experimental conditions, the experimenter publicly revealed subjects’ names and caste. In the task—solving mazes—in which performance was studied here, the low-caste subjects in the anonymous condition did not perform significantly differently from high-caste subjects; but when caste identity was publicly revealed in a mixed caste group, a significant caste gap emerged. The caste gap was due to a 20 percent decline in the average number of mazes solved by the low caste. The study shows that publicly revealing the social identity of an individual can change his behavior even when that information is irrelevant to payoffs. Our results are a generalization of the literature on stereotype threat. Like that literature, we find that individuals’ performance is more in accordance with the stereotype of the group when group membership is made salient in some way. Unlike that literature, salience in our experiments depends on the public revelation of social identity and more importantly, we do not argue that the domain of the tasks undertaken by † Discussants: Rachel Croson, University of Pennsylvania; Iris Bohnet, Harvard University; Stefano DellaVigna, University of California-Berkeley.